Decade-long protection of the mumps vaccine: Insights from a large-scale serological study. - Zixia Qian; Yueling Chen; Lilian Zeng; Chumin Liang; Weizhao Lin; Can Xiong; Xinxin Li; Yingyin Deng; Liang Chen; Ying Yang; Limei Sun; Jianfeng He; et al. (PLoS Neglected Tropical Diseases)
Background Serological surveys of mumps are important for estimating susceptibility in the population and for evaluating the effectiveness of current vaccination strategies. Methods A cross-sectional serological survey using an enzyme-linked immunosorbent assay was conducted on 5,147 participants in Guangdong, China, to evaluate the immunological effects of 2 doses of measles-mumps-rubella vaccine. In accordance with the instructions of the ELISA kit, the final readings represent the anti-mumps antibody titers, which are expressed in "NovaTec units". Results Of the 5,147 participants, 3,888 were positive for mumps IgG antibodies, with a seroprevalence of 75.54% (95% CI: 74.34%-76.71%). For each age group, the mumps IgG seroprevalence rates were 74.40%, 89.02%, 85.58%, 68.60%, 69.28%, 78.42%, and 80.63% for those <8 months, 8 months-2 years, 3-5 years, 6-17 years, 18-39 years, 40-59 years, and>=60 years, respectively. In terms of the percentage decreases in anti-mumps antibody titers, in the population receiving the 1-dose vaccine, there was a mean decrease of 2.06% per year. In the population receiving 2 doses of the vaccine, the mean annual decreases were 10.33% and reached protective thresholds of approximately 12.3 years. Conclusion The high mumps seroprevalence in the unvaccinated population revealed neglected hidden mumps infections. A time-lapse assay of IgG antibodies indicated that the mumps vaccine provided protection for one decade, which highlights that booster vaccinations may be needed in adults.